THE EFFECTIVENESS OF SONGS OF YOUTUBE VIDEOS IN IMPROVING PRONUNCIATION SKILL OF THE GARDE ELEVENTH STUDENTS AT SMK NEGERI 2 PALU - Irmayanti, Irmayanti; Mukrim, Mukrim; Wahyudin, Wahyudin; Hasyim, Zarkiani (e-Journal of ELTS (English Language Teaching Society), 2024)
The objective of this research was to prove that using Songs of YouTube Videos is effectiveness in improving pronunciation skill of the grade eleventh students at SMK Negeri 2 Palu. This research used a quasi-experimental research design. The sample of the research was 25 students from class XI BDP 1 (Bisnis Daring Pemasaran) as the experimental class and 25 students from class BDP 2 (Bisnis Daring Pemasaran) as the control class. The instruments used in this research were test, pretest and posttest. The result of the data analyzed showed that there is significant difference between the result of the pretest and posttest. The mean score of the pretest of experimental class was 45.2 while the control class was 46.8. After giving the treatment, the mean score of the experimental class in the posttest was 85.4 and the control class was 56.0. By applying 0.05 level of significance, the researcher found that the value of the t-counted (15.1) is higher than t-table (1.67). It means that the use of song of youtube videos is effective in improving pronunciation skill of the grade eleventh students at SMK Negeri 2 Palu.